Asian bond monitor June 2020. - Asian Development Bank. (Metro Manila, Philippines Asian Development Bank, 2020)
This edition of the Asia Bond Monitor reviews developments in emerging East Asian local currency bond markets and discusses how the financial sector can help fund the fight against the coronavirus disease (COVID-19). Local currency bonds outstanding in emerging East Asian markets climbed to USD16.3 trillion in the first quarter of 2020. Risks remain heavily tilted to the downside given uncertainty about the effects of COVID-19. A section on the financial sector and COVID-19 discusses the use of pandemic bonds and social bonds to mobilize resources and of fintech to support inclusive growth and pandemic resilience. A chapter on financial architecture and innovation examines whether banks or equity and debt markets are more conducive to innovation. It finds that a market-based financial system is more conducive.
Keywords: Bond market -- Asia -- Periodicals; Bonds -- Asia -- Statistics -- Periodicals; Government securities -- Asia -- Periodicals; Rate of return -- Asia -- Periodicals; Electronic books